2014
DOI: 10.1002/ajh.23650
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin trends do not predict changes in total body iron in patients with transfusional iron overload

Abstract: Ferritin levels and trends are widely used to manage iron overload and assess the efficacy of prescribed iron chelation in patients with transfusional iron loading. A retrospective cohort study was conducted in 134 patients with transfusion-dependent anemia, over a period of up to 9 years. To determine whether the trends in ferritin adequately reflect the changes in total body iron, changes in ferritin between consecutive liver iron measurements by magnetic resonance imaging (MRI) were compared to changes in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(66 citation statements)
references
References 21 publications
7
58
0
1
Order By: Relevance
“…These results are consistent with the previous reports of serum ferritin having a linear relationship with LIC at levels <1500 ng/mL. 14,15 In this study it appears that the impact of simple transfusion was obviated by LTE. We found no association between simple transfusion and serum ferritin or LIC.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with the previous reports of serum ferritin having a linear relationship with LIC at levels <1500 ng/mL. 14,15 In this study it appears that the impact of simple transfusion was obviated by LTE. We found no association between simple transfusion and serum ferritin or LIC.…”
Section: Discussionsupporting
confidence: 94%
“…14-16 A recent study found agreement between serum ferritin trends and MRI measures of LIC in only 38% of subjects, suggesting that MRI measures may be superior for identifying iron overload as compared with serum ferritin alone. 15 Data from chronically transfused SCD patients from the STOP and STOP2 trials, most of whom were on chelation therapy, consistently showed that ferritin levels <1500 ng/mL correlated with low LIC, whereas ferritin levels of >3000 ng/ mL predicted LIC > 10 mg/g DW. 14 This may be explained by rapid serum ferritin level changes at lower iron load (< 1500 ng/mL) with a slower and less predictable rate of change at moderate iron load (1500 to 3000 ng/mL).…”
Section: Introductionmentioning
confidence: 96%
“…Serum parameters (serum iron and transferrin saturation) gave way to the widely available serum ferritin, which is inexpensive and useful for routine clinical assessment. However ferritin is subject to many variations, and even when measured frequently, may not accurately reflect tissue iron burden [39]. Recently, scientific studies have led to better understanding of iron trafficking, including how iron accumulates in tissues which were not intended to store iron [40].…”
Section: Prolonging Survival: Transfusions and Chelationmentioning
confidence: 99%
“…However, increased serum ferritin is caused by several conditions, including inflammatory diseases, tissue damage, hematological malignancy, and immunodeficiency, and it does not accurately assess iron overload. 10,11 According to the clinical course shown in Fig. 4, the ferritin level did not improve following therapy for ATLL.…”
Section: Discussionmentioning
confidence: 99%